A 10-Year Retrospective Review of Salmonella Infections at the Children’s Hospital in London, Ontario - Tania Cellucci; Jamie A Seabrook; Yasmine Chagla; Susan L Bannister; Marina I Salvadori (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVES: To describe Salmonella infections in children presenting to the Children’s Hospital (London Health Sciences Centre, London, Ontario), to assess risk factors for infection and to examine whether younger children, particularly infants younger than 12 weeks of age, experience higher morbidity than older children.